(untitled) (Environmental Smoke, 2021)
A lodging facility for domestic dogs is a development that provides accommodation services among its main activities. Other services, such as the provision of natural food, of baths, and of shearing, among others, are also offered when required. The inn aims to care for animals during the absence of the pet owner. While the animals are adequately accommodated, the pet owners must be assured that their pets will be well cared for during the periods in which they plan to be absent. The “DOGPLACE” Inn, a well-managed business, indicates that the branch of entertainment for domestic dogs can be a promising investment. It is important that the business owner and manager possess a strong liking of animals and demonstrate satisfaction in dealing with people, as they will need to maintain constant communication with the pet owner. During times of pandemics, the sanitation of the inn, and knowledge of the latest scientific information concerning the transmission of the ailment of most concern, contribute to the suitability of the business. At “DOGPLACE” Inn, sanitation of all spaces is constant, contributing to avoid “Covid-19, the illness caused by the new coronavirus SARS-CoV-2. Recent news in the international media accounting cases of positive infections in dogs for Covid-19 have caused much worry among dog owners in general. Veterinarians elucidate that recommendations remain the same as the good sanitation practices among humans. Until the present time, there is no evidence that in natural conditions pets will become ill by contraction of Covid-19, nor that they are able to transmit the illness to human beings. The whole issue nevertheless points to the importance of promoting prevention actions aiming to maintain the health of animals and their human guardians in the “DOGPLACE” Inn. Frequent visits of pets to the veterinarian are also recommended.